Tuning the room temperature ferromagnetism in Fe5GeTe2 by arsenic substitution. (17th November 2021) - May, Andrew F; Yan, Jiaqiang; Hermann, Raphael; Du, Mao-Hua; McGuire, Michael A
Abstract: In order to tune the magnetic properties of the cleavable high-Curie temperature ferromagnet Fe 5 − x GeTe2, the effect of increasing the electron count through arsenic substitution has been investigated. Small additions of arsenic (2.5% and 5%) seemingly enhance ferromagnetic order in polycrystalline samples by quenching fluctuations on one of the three magnetic sublattices, whereas larger As concentrations decrease the ferromagnetic Curie temperature ( T C ) and saturation magnetization. This work also describes the growth and characterization of Fe4.8 AsTe2 single crystals that are structurally analogous to Fe 5 − x GeTe2 but with some phase stability complications. Magnetization measurements reveal dominant antiferromagnetic behavior in Fe4.8 AsTe2 with a Néel temperature of T N ≈ 42 K. A field-induced spin-flop below T N results in a switch from negative to positive magnetoresistance, with significant hysteresis causing butterfly-shaped resistance loops. In addition to reporting the properties of Fe4.8 AsTe2, this work shows the importance of manipulating the individual magnetic sublattices in Fe 5 − x GeTe2 and motivates further efforts to control the magnetic properties in related materials by fine tuning of the Fermi energy or crystal chemistry.